Neutral zone and oral submucous fibrosis - Shaista Afroz; Sajjad Abdur Rahman; Indresh Rajawat; A K Verma (Wolters Kluwer Medknow Publications, 2012)
Oral submucous fibrosis is a premalignant condition in which rigidity of the lip, tongue, and palate results in reduced mouth opening and tongue movement. Limited mouth opening, mucosal rigidity, and reduced salivary flow makes prosthodontic procedures difficult in these patients and affects the stability, retention, and the support of removable prostheses. The burning sensation in the mouth that these patients experience reduces the tolerance to prostheses. We report a case of oral submucous fibrosis where the conventional neutral zone technique with certain modifications was utilized to rehabilitate a completely edentulous patient with this condition.